Evaluating The Feasibility of Replacing Official Vehicle Facility (ROVF) in Balangan Regency: Case Study In Cost-Benefit Analysis - Rahma Yuliani; Zaki Mubarak; Arifah Arifah; Atma Hayat (International Business and Accounting Research Journal, 2023)
Official vehicles are facilities that support the mobility of local officials. There are three options for acquiring those vehicles: purchasing, renting, or replacing official vehicle facility (ROVF) options. This study aimed to evaluate the efficiency, effectiveness, and feasibility of ROVF in the Balangan Regency. This research is a case study involving data analysis techniques using documentation and the literature. The analysis method used was a cost-benefit analysis. There are six stages of cost-benefit analysis in this study: setting goals to be achieved, determining alternatives to be used in the analysis, identifying the cost-benefit component of each alternative that has been set, predicting the impact quantitatively during the time of the project/policy, assessing the monetary value of all impacts (benefits and costs) that have been identified and detailed quantitatively, drawing conclusions, and making recommendations. The research findings indicate that ROVF reduces regional revenue and expenditure budget burden compared to acquiring official vehicles through purchase and rental options. ROVF also enhances officials' performance. The analysis concludes that ROVF in the Balangan Region is feasible.